Hydrodynamics of linear acceleration in bluegill sunfish, Lepomis macrochirus - Wise, Tyler N. (J Exp Biol, 2018)
In their natural habitat, fish rarely swim steadily. Instead they frequently accelerate and decelerate. Relatively little is known about how fish produce extra force for acceleration in routine swimming behavior. In this study, we examined the flow around bluegill sunfish Lepomis macrochirus during steady swimming and during forward acceleration, starting at a range of initial swimming speeds. We found that bluegill produce vortices with higher circulation during acceleration, indicating a higher force per tail beat, but they do not substantially redirect the force. We quantified the flow patterns using high speed video and particle image velocimetry and measured acceleration with small inertial measurement units attached to each fish. Even in steady tail beats, the fish accelerates slightly during each tail beat, and the magnitude of the acceleration varies. In steady tail beats, however, a high acceleration is followed by a lower acceleration or a deceleration, so that the swimming speed is maintained; in unsteady tail beats, the fish maintains the acceleration over several tail beats, so that the swimming speed increases. We can thus compare the wake and kinematics during single steady and unsteady tail beats that have the same peak acceleration. During unsteady tail beats when the fish accelerates forward for several tail beats, the wake vortex forces are much higher than those at the same acceleration during single tail beats in steady swimming. The fish also undulates its body at higher amplitude and frequency during unsteady tail beats. These kinematic changes likely increase the fluid dynamic added mass of the body, increasing the forces required to sustain acceleration over several tail beats. The high amplitude and high frequency movements are also likely required to generate the higher forces needed for acceleration. Thus, it appears that bluegill sunfish face a trade-off during acceleration: the body movements required for acceleration also make it harder to accelerate.